EDUCATION OF THE HAZARDS OF SMOKING WITH MEDIA LEAFLET TO RESIDENTS OF SEGOROYOSO 1 RT 1 PLERET BANTUL - Novalia, Prima Dewi; Emma Dwi Jatmika, Septian (LPPM Univ. Ibn Khaldun Bogor, 2022)
Smoking is an activity that we often see in society. The danger of smoking is a threat to human life, where we find a lot of smoking behavior both in the home environment and outside the home environment. Men tend to have more smoking behavior, even though men are the heads of families in the household who should be role models for children. The implementation method carried out in this service is divided into 3 stages, namely the preparation stage which consists of observation and situation analysis, the planning stage consists of program development and the evaluation stage. The evaluation stage is carried out by presenting a pretest and posttest which is then processed using SPSS. After the education was carried out, it was found that the posttest score increased by 23%, which can be said that the service was successful.